The newly installed IBIL (Ion Beam Induced Luminescence) set-up at CEDAD-University of Salento: design and first applications on perovskite. (1st June 2022) - Quarta, G.; Caricato, A.P.; Provenzano, C.; Marra, M.; Albanese, E.; Vasco, G.; Martino, M.; Maruccio, L.; Calcagnile, L.
Abstract: We present the design and implementation of the new Ion Beam Induced Luminescence set-up recently installed and tested at the Centre of Applied Physics, Dating and Diagnostics of the University of Salento. The set-up allows the irradiation of samples at atmospheric pressure with MeV protons produced by a 3 MV Tandetron accelerator and extracted in air through a kapton membrane. Ion beam induced luminescence is collected by an optical fiber and analyzed by an imaging spectrometer. Simultaneously, characteristic X-Rays emitted by the sample are detected by a Silicon Drift Detector (SSD) detector. The system also allows combined photoluminescence measurements by using an excitation laser focused onto the samples. First applications in the analysis of all-inorganic perovskites (CsPbBr3 ) deposited by PLD (Pulsed Laser Deposition) are presented.